Mirtazapine Augmentation for Selective Serotonin Reuptake Inhibitor-Induced Sexual Dysfunction: A Retropective Investigation - Atmaca, Murad; Korkmaz, Sevda; Topuz, Mehtap; Mermi, Osman (Korean Neuropsychiatric Assoc, 2011)
The aim of the present study was to retrospectively identify sexual dysfunction changes in the patients under mirtazapine-augmented serotonin reuptake inhibit (SSRI) treatment. The study comprised medical records of 20 outpatients, under mirtazapine-augmented SSRI treatment for their major depressive disorder, who had been selected among the patients that had developed sexual dysfunction to previous treatment as monotherapy, with SSRI for at least six weeks. These drugs were maintained and mirtazapine were added (15-45 mg/day). There was a significant difference in scores between baseline and week 4 or week 8 on the both Hamilton Depression Rating and Arizona Sexual Experience Scale. According to Clinical Global Impression-Improvement, 68.4% of the patients were responders. The use of low-dose mirtazapine as an add-on treatment to SSRIs appears to be an effective and well-tolerated augmenttaion for sexual dysfunction caused by SSRIs. Psychiatry Investig 2011;8:55-57
Keywords: Mirtazapine; Sexual dysfunction; SSRI